Dental Whitening: Self-Referred Needs versus Professional Indication - Jéssica de Oliveira Sotero Cavalcanti; Inaldo Nogueira de Oliveira Neto; Marlon Ferreira Dias; Paulo Cardoso Lins-Filho; Renata Pedrosa Guimarães (Association of Support to Oral Health Research (APESB), 2022)
Objective: To analyze the self-reported need of patients compared to professional indications for tooth whitening. Material and Methods: Initially, 58 undergraduate students responded to a form that highlighted the question: "Do you think you need to have your teeth whitened?" Among those who answered positively to the previous question, ten individuals were photographed with their smiles. In addition, they were asked to point out, on the Vita 3D-Master scale, which color they believed their teeth had, a value that was compared to the actual color obtained by a spectrophotometer. Finally, the photographs were presented to dentists, who were asked about the indication or not of the whitening treatment. Results: Most interviewees (63.8%) self-reported the need for whitening, as well as there was a greater incidence of a positive indication among professionals (53.9%). Pearson's Chi-square test revealed a relationship between patient gender and the training course on the desire to have teeth whitened. Among the professionals, the specialty, as well as time since graduation, interfered in the indication for whitening. Conclusion: Professionals and patients share the aesthetic ideal directly related to light teeth; most patients self-perceive the color of their teeth darker than it actually is; the opinion about the color of the teeth has an extremely subjective character and varies greatly from one professional to another.